EFFECT OF BUSINESS VOLUME AND NUMBER OF MEMBERS ON ‘SHU’ OF SHARIA SAVINGS AND LOANS COOPERATIVE MEMBERS DURING THE PANDEMIC PERIOD IN EAST JAVA - Aminudin, Muhammad Sulton; Chandraningtyas, Iva (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 8 No 1 (2022): The 8th International Conference Of Islamic Economics And Business (ICONIES 2022), 2022)
This study aims to measure the effect of business volume and number of members on the remaining operating results (SHU) or dividend, of sharia savings and loan cooperatives in East Java during 2020. With a detailed statistical description, the discussion will help novice researchers study the results of statistical analyses. The research design used is causal quantitative. The research subjects are cooperatives registered in the ODS system of the Department of Cooperatives and SMEs of East Java Province. The objects studied are business volume, number of members, and SHU. The sampling technique used is purposive sampling with a total of 244 cooperatives, with the criteria being sharia savings and loan cooperatives. Data were collected by recording documents and then analyzed by multiple linear regression analysis. The results showed that during the pandemic, (1) the volume of business and the number of members had a significant effect on SHU, (2) The number of members had a positive and significant effect on SHU, and (3) the number of members had a more positive and significant influence on SHU compared to the volume of business.